Somatosensory abnormalities after infection with SARS-CoV-2 – A prospective case-control study in children and adolescents - Eitner, Lynn; Maier, Christoph; Brinkmann, Folke; Schlegtendal, Anne; Knoke, Leona; Enax-Krumova, Elena; Lücke, Thomas (Frontiers in Pediatrics, 2022)
Background Long-term neurological complaints after SARS-CoV-2 infection occur in 4–66% of children and adolescents. Controlled studies on the integrity of the peripheral nerve system are scarce. Therefore, we examined the somatosensory function in children and adolescents after SARS-CoV-2 infection in a case-control study compared with age-matched individuals. Methods 81 subjects after SARS-CoV-2 infection (n=44 female, 11·4±3·5y, n=75 SARS-CoV-2 seropositive, n=6 PCR positive during infection and SARS-CoV-2 seronegative at the time point of study inclusion, n=47 asymptomatic infection) were compared to 38 controls without SARS-CoV-2 infection (26 female, 10·3±3·4y, n=15 with other infection within last 6 months). After standardised interviews and neurological examinations, large fibre (tactile and vibration detection thresholds) and small fibre (cold and warm detection thresholds, paradoxical heat sensation) functions were assessed on both feet following a validated protocol. After z-transformation of all values, all participants were compared to published reference values regarding the number of abnormal results. Additionally, the mean for all sensory parameters values of both study groups were compared to an ideal healthy population (with z-value 0±1), as well as with each other, as previously described. Statistical analyses: t-test, Chi-squared test and binominal test. Findings None of the controls, but 27 of the 81 patients (33%, p<0·001) reported persistent complaints 2·71·9 (0·8-8·5) months after SARS-CoV-2 infection, most often reduced exercise capacity (16%), fatigue (13%), pain (9%), or paraesthesia (6%). Reflex deficits or paresis were missing, but somatosensory profiles showed significantly increased detection thresholds for thermal (especially warm) and vibration stimuli compared to controls. Approximately 36% of the patients after SARS-CoV-2, but none of the controls revealed an abnormal sensory loss in at least one parameter (p<0·01). Sensory loss was characterised in 26% by large and 12% by small fibre dysfunction, the latter appearing more frequently in children with prior symptomatic SARS-CoV-2 infection. Myalgia/paraesthesia was indicative of somatosensory dysfunction. In all eight re-examined children, the nerve function recovered after 2–4 months. Interpretation This study provides evidence that in a subgroup of children and adolescents previously infected with SARS-CoV-2, regardless of their complaints, the function of large or small nerve fibres is presumably reversibly impaired.